E-Commerce: The New Art Market - Rani, Archana (Journal of Commerce and Trade, 2017)
Twenty first century witnessed a drastic change in selling or buying of paintings online. India is no exception in this regard. In the past few years, selling online paintings has become a new trend to look up in India. Many young artists now believe that it is better to put art online for sale. Today, various art exhibitions provide a wide platform for the development of art profession and State support likewise has developed in diverse organizations, such as an artist’s studio, open art exhibitions and online galleries. The greater part of the famous artist’s show in various displays of their works from all over the nation and art exhibitions reflects the nation’s contemporary art practice. Throughout the most recent decade, with the digitalisation of art and advancement of Indian economic development of the art market has significantly reached its highest peak. On account of developing markets, the nation where the art has a place and their destiny in the worldwide field is straightforwardly affected by the quirks of the country’s economy.